2005
DOI: 10.1900/rds.2005.2.121
|View full text |Cite
|
Sign up to set email alerts
|

B Cells in Autoimmune Diabetes

Abstract: ■ AbstractAutoantibodies have been used as good markers for the prediction of future development of type 1 diabetes mellitus (T1DM), but are not thought to be pathogenic in this disease. The role of B cells that produce autoantibodies in the pathogenesis of human T1DM is largely unknown. In the non-obese diabetic (NOD) mouse model of autoimmune diabetes, it has been shown that B cells may contribute multifariously to the pathogenesis of the disease. Some aspects of deficiencies of B cell tolerance may lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 96 publications
(120 reference statements)
1
40
0
Order By: Relevance
“…These findings have recently been confirmed using the PPI [15][16][17][18][19][20][21][22][23][24] clone and an additional HLA-A2-restricted PPI clone, PPI [3][4][5][6][7][8][9][10][11] [106]. These clones killed beta-cells by requiring a direct interaction via MHC class I and utilizing perforin and granzymes.…”
Section: Effector Mechanisms Utilized By Human Auto-reactive Ctlsmentioning
confidence: 83%
See 3 more Smart Citations
“…These findings have recently been confirmed using the PPI [15][16][17][18][19][20][21][22][23][24] clone and an additional HLA-A2-restricted PPI clone, PPI [3][4][5][6][7][8][9][10][11] [106]. These clones killed beta-cells by requiring a direct interaction via MHC class I and utilizing perforin and granzymes.…”
Section: Effector Mechanisms Utilized By Human Auto-reactive Ctlsmentioning
confidence: 83%
“…Recent studies have clarified this and demonstrated that diabetes cannot be transferred by antibody or B cells alone [10]. Instead, B cells contribute primarily as antigenpresenting cells [10][11][12]. Using a series of transgenic and mutant mice with increased B cell activation, Silva et al demonstrated that B cells act to enhance the accumulation and function of isletreactive CD4 + T cells promoting diabetes development [10].…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other cells of the immune system also play a relevant role in the development of the disease. In this regard, it is believed that B lymphocytes may act both as APCs for autoreactive T lymphocytes and/or as producers of autoantibodies against several ␤ cell autoantigens (5,6).…”
mentioning
confidence: 99%